The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Environmental and Spatial Influences on Biogeography and Community Structure of Saltmarsh Benthic Diatoms - Craig J. Plante; Kristina Hill-Spanik; Maxwell Cook; Connor Graham (Estuaries and Coasts, 2021)

Under what circumstances does the capture and tagging of wild Atlantic salmon Salmo salar smolts affect probability of return as adults? - William D. Riley; Anton T. Ibbotson; Stephen D. Gregory; Ian C. Russell; Rasmus B. Lauridsen; William R. C. Beaumont; Alastair C. Cook; David L. Maxwell (Journal of Fish Biology, 2018)
Adult return rates for wild Atlantic salmon Salmo salar smolts captured in a rotary screw trap and tagged with coded wire (CW) tags were compared with a control group, using detections from passive integrated transponder (PIT) antennae systems over 7 years in a small chalk stream in southern England, U.K. Compared with control smolts, capture and CW‐tagging of experimental smolts affected detected return rates only under certain conditions, with a decreased return probability for smolts caught and tagged following mild winter river temperature anomalies and during the night. Similarly, analysis of the experimental smolts revealed that capture and CW‐tagging following mild winters decreased their probability of return as adults. There were also marginal positive effects of length at PIT‐tagging as parr and length at CW‐tagging as smolts, on individual probability of return as adult. The results support the hypothesis that the effect of procedures involving the capture and tagging of migrating wild S. salar smolts will vary with the circumstances under which they are performed. The implications of the findings are considered in the context of ongoing investigations to derive and report marine return rates for S. salar in support of national and international stock assessments and in developing best practice.